Georgia Financial Sector Assessment - World Bank; International Monetary Fund (World Bank, Washington, DC, 2022)
A joint IMF and World Bank team conducted virtual missions to Georgia during January-February 2021 and May-June 2021, to update the findings of the Financial Sector Assessment Program (FSAP) conducted in 2014. This report summarizes the main findings of the mission, identifies key financial sector vulnerabilities and developmental issues, and provides policy recommendations